The Trichoderma harzianum Kelch Protein ThKEL1 Plays a Key Role in Root Colonization and the Induction of Systemic Defense in Brassicaceae Plants - Poveda, Jorge; Hermosa, Rosa; Monte, Enrique; Nicolás, Carlos (Frontiers in Plant Science, 2019)
The fungal genus Trichoderma includes strains with biocontrol and/or biostimulant potential and is recognized as a source of genes with biotechnological value. In a previous study the Kelch domain protein, encoded by the Thkel1 gene of Trichoderma harzianum T34, was found to confer tolerance to salt stress when expressed in plants of Arabidopsis thaliana. In the present work, we have overexpressed Thkel1 in rapeseed plants in order to generate an additional biotechnological tool for analyzing the role of this gene in Trichoderma-plant interactions. The overexpression of this gene in Brassicaceae plants improves responses to pathogens through the induction of systemic defenses mediated by jasmonic acid, facilitates root colonization by modulating the myrosinase activity, and, as a result, increases plant productivity. These effects were also observed in Thkel1 overexpressing plants subjected to abiotic stress conditions. Additionally, the differences detected in root colonization levels by T. harzianum wild type and Thkel1 silenced transformants between Arabidopsis or rapeseed and tomato plants indicate that ThKEL1 interacts in different ways in Brassicaceae and non-Brassicaceae plants.